Impaired learning and memory in CD38 null mutant mice. Issue 1 (December 2016) - Kim, Somi; Kim, TaeHyun; Lee, Hye-Ryeon; Jang, Eun-Hye; Ryu, Hyun-Hee; Kang, Minkyung; Rah, So-Young; Yoo, Juyoun; Lee, Bolam; Kim, Jae-Ick; Lim, Chae; Kim, Sang; et al.
Abstract CD38 is an enzyme that catalyzes the formation of cyclic ADP ribose and nicotinic acid adenine dinucleotide phosphate, both of which are involved in the mobilization of Ca2+ from intracellular stores. Recently, CD38 has been shown to regulate oxytocin release from hypothalamic neurons. Importantly, CD38 mutations are associated with autism spectrum disorders (ASD) and CD38 knockout (CD38−/− ) mice display ASD-like behavioral phenotypes including deficient parental behavior and poor social recognition memory. Although ASD and learning deficits commonly co-occur, the role of CD38 in learning and memory has not been investigated. We report that CD38−/− mice show deficits in various learning and memory tasks such as the Morris water maze, contextual fear conditioning, and the object recognition test. However, either long-term potentiation or long-term depression is not impaired in the hippocampus of CD38−/− mice. Our results provide convincing evidence that CD38−/− mice show deficits in various learning and memory tasks including spatial and non-spatial memory tasks. Our data demonstrate that CD38 is critical for regulating hippocampus-dependent learning and memory without modulating synaptic plasticity.